Arabidopsis microRNA expression regulation in a wide range of abiotic stress responses - Barciszewska-Pacak, Maria; Milanowska, Kaja; Knop, Katarzyna; Bielewicz, Dawid; Nuc, Przemyslaw; Plewka, Patrycja; Pacak, Andrzej M.; Vazquez, Franck; Karlowski, Wojciech; Jarmolowski, Artur; Szweykowska-Kulinska, Zofia (Frontiers in Plant Science, 2015)
Arabidopsis microRNA expression regulation was studied in a wide array of abiotic stresses such as drought, heat, salinity, copper excess/deficiency, cadmium excess and sulphur deficiency. A home-built RT-qPCR mirEX platform for the amplification of 289 Arabidopsis microRNA transcripts was used to study their response to abiotic stresses. Small RNA sequencing, Northern hybridization and TaqMan® microRNA assays were performed to study the abundance of mature microRNAs. A broad response on the level of primary miRNAs (pri-miRNAs) was observed. However, stress response at the level of mature microRNAs was rather confined. The data presented show that in most instances, the level of a particular mature miRNA could not be predicted based on the level of its pri-miRNA. This points to an essential role of posttranscriptional regulation of microRNA expression. New Arabidopsis microRNAs responsive to abiotic stresses were discovered. Four microRNAs: miR319a/b, miR319b.2, and miR400 have been found to be responsive to several abiotic stresses and thus can be regarded as general stress-responsive microRNA species.